Implementasi Program Jaminan Persalinan (Jampersal) di Puskesmas Jember Kidul Kecamatan Kaliwates, Kabupaten Jember - Salam, Miranti; Rahmawati, Atik (e-Sospol, 2015)
Abstract The government launched a program based Permenkes Jampersal No. 631/Menkes/per/III/2011 implemented in order to accelerate the achievement of national health development and the Millennium Development Goals (MDGs), which aim to maternal and child mortality can be reduced. In order to service Jampersal Program, the Jember Kidul Local Government Clinic seeks to provide maximum health services to the community especially on the poor without exception to be able to maintain and improve public health by pressing AKI and AKB. Jember Kidul Local Government Clinic is a Local Government Clinic in the district Kaliwates with the rating of visitors amounted to 30.987 visitors and visitors Jampersal most receivers are in the period, May 2011 to April 2012 as many as 815 visitors. Unlike the other Local Government Clinic average about 534 to 723 visitors Jampersal receiver (Dinkes Jember, 2011-2012). Services provided from the Jember Kidul Local Government Clinic implementing has led to skyrocketing impact patient visits, especially pregnant women.